2021
DOI: 10.1007/s11104-021-05082-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term maize-Desmodium intercropping shifts structure and composition of soil microbiome with stronger impact on fungal communities

Abstract: Purpose Push–pull is an intercropping technology that is rapidly spreading among smallholder farmers in Sub-Saharan Africa. The technology intercrops cereals with Desmodium to fight off stem borers, eliminate parasitic weeds, and improve soil fertility and yields of cereals. The above-ground components of push–pull cropping have been well investigated. However, the impact of the technology on the soil microbiome and the subsequent role of the microbiome on diverse ecosystem benefits are unknown. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…In a separate study, the frequency of occurrence of a mycotoxin-producing fungus Aspergillus flavus was lower in push-pull than maize monoculture plots (Maxwell et al, 2017). These findings are in line with our previous study where we show that push-pull farming and Desmodium intercropping in cereal farming impact diversity of fungal communities more than bacteria (Mwakilili et al, 2021), manipulation of fungal communities in the soil to promote competitive beneficial filamentous fungi has been established as a method to manage mycotoxins in cereals (Sarrocco et al, 2019). In a similar vein, another study demonstrated that maize growing on soil from long-term push-pull plots produced higher amounts of secondary metabolites and experienced lesser herbivory than maize growing on soil from corresponding maize monoculture plots (Mutyambai et al, 2019).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a separate study, the frequency of occurrence of a mycotoxin-producing fungus Aspergillus flavus was lower in push-pull than maize monoculture plots (Maxwell et al, 2017). These findings are in line with our previous study where we show that push-pull farming and Desmodium intercropping in cereal farming impact diversity of fungal communities more than bacteria (Mwakilili et al, 2021), manipulation of fungal communities in the soil to promote competitive beneficial filamentous fungi has been established as a method to manage mycotoxins in cereals (Sarrocco et al, 2019). In a similar vein, another study demonstrated that maize growing on soil from long-term push-pull plots produced higher amounts of secondary metabolites and experienced lesser herbivory than maize growing on soil from corresponding maize monoculture plots (Mutyambai et al, 2019).…”
Section: Introductionsupporting
confidence: 92%
“…plots harboured a substantial percentage of the significantly abundant taxa; these are D. uncinatum, D. incanum and D. intortum (Figure 7.) As in our previous long-term study on maize-Desmodium intercropping soils (Mwakilili et al, 2021) where we investigated impact of push-pull technology that employs perennial Desmodium spp. intercrops, soils diverged more in fungal than bacterial communities.…”
Section: Differential Abundances Of Individual Taxamentioning
confidence: 99%
See 1 more Smart Citation
“…Paraglomus, was identified in crop rotation. Mwakilili et al (2021) demonstrated that the genus Glomus was enriched in maize monoculture plots. The abundance of Glomeromycota fungi was significantly negatively correlated with soil pH which was lower in monoculture.…”
Section: Discussionmentioning
confidence: 99%
“…This begs the question of why Desmodium releases these volatiles constitutively. Push-pull maize- Desmodium intercropping causes substantial shifts in below-ground ecosystems, including increased soil microbe diversification, increased soil nitrogen and carbon, increased plant defense through plant-soil feedback, and suppression of parasitic weeds and pathogenic microbes 22,23 . We therefore verified if the ‘constitutive’ release of volatiles was, in fact, induced or enhanced by soil-borne interactions.…”
Section: Main Textmentioning
confidence: 99%